Minor tobacco alkaloids as biomarkers for tobacco use: comparison of users of cigarettes, smokeless tobacco, cigars, and pipes. - Jacob, P (1999)
OBJECTIVES: This study (1) determined levels of various tobacco alkaloids in commercial tobacco products. (2) determined urinary concentrations, urinary excretion, and half-lives of the alkaloids in humans; and (3) examined the possibility that urine concentrations of nicotine-related alkaloids can be used as biomarkers of tobacco use. METHODS: Nicotine intake from various tobacco products was determined through pharmacokinetic techniques. Correlations of nicotine intake with urinary excretion and concentrations of anabasine, anatabine, nornicotine, nicotine, and cotinine were examined. By using urinary excretion data, elimination half-lives of the alkaloids were calculated. RESULTS: Alkaloid levels in commercial tobacco products, in milligrams per gram, were as follows: nicotine, 6.5 to 17.5; nornicotine, 0.14 to 0.66; anabasine, 0.008 to 0.030; and anatabine, 0.065 to 0.27. Measurable concentrations of all alkaloids were excreted in the urine of most subjects smoking cigarettes, cigars, and pipes and using smokeless tobacco. Correlations between nicotine intake and alkaloid concentrations were good to excellent. CONCLUSIONS: Anabasine and anatabine, which are present in tobacco but not in nicotine medications, can be used to assess tobacco use in persons undergoing nicotine replacement therapy.